Virtual Reality Design For Introduction To Ternate City Culture - Muhammad Ridha Albaar; Hairil Kurniadi Siradjudin; Seh Turuy; Yasir Muin (Jurnal Ilmiah ILKOMINFO - Ilmu Komputer & Informatika, 2026)
Abstract: Culture is a priceless heritage that reflects the identity, values, and history of a community. Ternate City, as one of the historic cities in Eastern Indonesia, boasts an abundant cultural heritage, including customs, traditional arts, and sites dating back to the Ternate Sultanate. One important cultural site is Kalamata Fort, which preserves local historical and cultural values. However, the influence of globalization and the lack of innovative media for promoting culture have led to a low level of public understanding and appreciation of this cultural heritage, especially among the younger generation.This research aims to design a virtual reality (VR)-based learning medium that visually and interactively displays the Kalamata Fort tourist attraction as an educational tool for cultural awareness. VR technology was chosen for its ability to provide an engaging, immersive experience, allowing users to explore the fort's environment and understand its historical values. The research method included collecting cultural data through observation, interviews, literature review, and documentation, which was then processed into a 3D model and integrated into the VR platform. The design results indicate that VR can be an effective medium for increasing public interest, understanding, and pride in local culture. With this approach, it is hoped that Kalamata Fort will not only be known as a historical site, but also as a technology-based educational facility that strengthens the cultural identity of Ternate City.Keywords: Virtual Reality, Local Culture, Kalamata Fort, Ternate City, Educational Media.